2019
DOI: 10.3171/2019.5.focus19272
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an infection prevention bundle is associated with reduced surgical site infections in cranial neurosurgery

Abstract: OBJECTIVEThe objective of this study was to quantify surgical site infection (SSI) rates after cranial neurosurgery in a tertiary care hospital, identify risk factors for SSI, and evaluate the impact of standardized surveillance and an infection prevention bundle (IPB).METHODSThe authors compared SSI rates during 7 months before and after the intervention. The IPB included standardized patient preparation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…According to studies in Europe, the most common infection types are pneumonia, surgical-site infections, and gastrointestinal infections [7]. Other studies showed that pneumonia, bloodstream infection and central venous infection were the most common types [9]. The ndings of this study were similar to the other studies for the types of infection, including pneumonia (65.3%), primary bloodstream infection (13.7%), central nervous system infections (8.4%).…”
Section: Infection Typessupporting
confidence: 81%
“…According to studies in Europe, the most common infection types are pneumonia, surgical-site infections, and gastrointestinal infections [7]. Other studies showed that pneumonia, bloodstream infection and central venous infection were the most common types [9]. The ndings of this study were similar to the other studies for the types of infection, including pneumonia (65.3%), primary bloodstream infection (13.7%), central nervous system infections (8.4%).…”
Section: Infection Typessupporting
confidence: 81%
“…In cases of skull trauma, chronic bone flap infection or bone flap resorption, where the bone flap is not reusable owing to multiple fragments, mature biofilm or aseptic bone necrosis, a synthetic cranioplasty is used (polyether ether ketone [PEEK], poly methyl methacrylate [PMMA] or titanium) [34,35]. Risk factors for infection are diabetes, presence of an EVD, CSF leakage, intracerebral haematoma and tumour surgery [36][37][38][39][40][41]. Craniotomy-and cranioplasty-associated infections usually manifest early after surgery (within the first month) and most commonly are caused by pathogens of the skin flora, namely staphylococci [36][37][38][39][42][43][44].…”
Section: Specific Infections Craniotomy-and Cranioplasty-associated Infectionsmentioning
confidence: 99%
“…The incidence of CNS infection was also high in our patients. removing unnecessary drainage/ monitoring intracranial tubes [37], antibiotic prophylaxis might be helpful for the prevention of meningitis and surgical site infection after craniotomy [38,39].…”
Section: Discussionmentioning
confidence: 99%